Synthesis of a Series of Non‐Symmetric Bispyridinium and Related Compounds and Their Affinity Characterization at the Nicotinic Acetylcholine Receptor. (27th November 2018) - Rappenglück, Sebastian; Sichler, Sonja; Höfner, Georg; Wein, Thomas; Niessen, Karin V.; Seeger, Thomas; Paintner, Franz F.; Worek, Franz; Thiermann, Horst; Wanner, Klaus T.
Abstract: The current standard therapy to counteract organophosphate intoxication is not effective in equal measure against all types of organophosphorus compounds (OPCs), as the outcome of oxime‐induced reactivation of inactivated acetylcholinesterase (AChE) strongly depends on the particular OPC. In case the reactivation is insufficient, acetylcholine concentrations that rise to pathophysiological levels force the nicotinic acetylcholine receptor (nAChR) into a desensitized state and hence a functionally inactive state. As a consequence, neurotransmission is irreversibly disrupted at the neuromuscular junction. Previous electrophysiological studies identified the symmetric bispyridinium compound 1, 1′‐(propane‐1, 3‐diyl)bis[4‐( tert ‐butyl)pyridin‐1‐ium] diiodide (MB327) as a re‐sensitizer of the desensitized nAChR. MB327 is thereby capable of restoring the functional activity. Very recently, in silico modeling studies suggested non‐symmetric derivatives of MB327 as potential re‐sensitizers with enhanced binding affinity and thus possible enhanced efficacy. In this study, 26 novel non‐symmetric bispyridinium compounds and related derivatives were synthesized. For the synthesis of the highly polar target compounds in sufficient quantities, newly developed and highly efficient two‐step procedures were used. Compounds were characterized in terms of their binding affinity toward the MB327 binding site at the nAChR using recently developed mass spectrometry (MS) Binding Assays. Regarding structure–affinity relationships at the MB327 binding site, the presence of two quaternary aromatic nitrogen centers as well as pyridinium systems with a tert ‐butyl group at the 4‐position or a NMe2 group at the 3‐ or 4‐positions appeared to be beneficial for high binding affinities. Abstract : Advancing toward new nAChR re‐sensitizers ! Based on in silico modeling results, a series of 26 non‐symmetric analogues of bispyridinium lead compound MB327 was synthesized and characterized in terms of binding affinity at the nicotinic acetylcholine receptor (nAChR) using our recently developed MS Binding Assays. We developed new structure–affinity relationships, providing a comprehensive groundwork for the design of novel nAChR re‐sensitizers.